2016
DOI: 10.1002/clen.201500415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Non‐Ionic Surfactant on Xylene Removal in a Scoria‐Compost‐Based Biofilter

Abstract: The effect of a non-ionic surfactant, Tween-20, on xylene removal performance of a previously acclimated scoria-compost-based biofilter was evaluated. In the presence of the surfactant, the maximum elimination capacities (EC max ) of 71.0, 84.1, and 93.6 g m À3 h À1 were obtained for xylene inlet loading rates (ILRs) of 114.9, 124.1, and 197.1 g m À3 h À1 at empty bed residence times (EBRTs) of 40, 60, and 90 s, respectively. When the biofilter was fed the nutrient solution with Tween-20, the average removal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…According to Fan et al, the value of f ( X v ) depends on the biomass concentration in the biofilm ( X v ) as Equation : f()Xv=Db,iDw,i=10.43Xv0.9211.19+0.27Xv0.992emi=Xylene,O2 where D b , i and D w , i are the diffusion coefficients of compound i in biofilm and water (m 2 s −1 ), respectively. There was no accumulation of biomass on the filter bed. Our experiments showed that the pressure drop values were less than 4 mm water and almost no clogging were seen to occur within the biofilter during the entire experiments . Biomass properties (thickness, specific surface area and kinetic coefficients) were uniform and constant along the bed under different operating conditions. There was no oxygen (O 2 ) supply limitation because O 2 was abundantly present and was more readily transferred than xylene. Adsorption of xylene onto the packing material was assumed to be negligible.…”
Section: Methodsmentioning
confidence: 82%
See 4 more Smart Citations
“…According to Fan et al, the value of f ( X v ) depends on the biomass concentration in the biofilm ( X v ) as Equation : f()Xv=Db,iDw,i=10.43Xv0.9211.19+0.27Xv0.992emi=Xylene,O2 where D b , i and D w , i are the diffusion coefficients of compound i in biofilm and water (m 2 s −1 ), respectively. There was no accumulation of biomass on the filter bed. Our experiments showed that the pressure drop values were less than 4 mm water and almost no clogging were seen to occur within the biofilter during the entire experiments . Biomass properties (thickness, specific surface area and kinetic coefficients) were uniform and constant along the bed under different operating conditions. There was no oxygen (O 2 ) supply limitation because O 2 was abundantly present and was more readily transferred than xylene. Adsorption of xylene onto the packing material was assumed to be negligible.…”
Section: Methodsmentioning
confidence: 82%
“…The details of biofilter setup were described elsewhere . Briefly, experiments were performed in a four‐stage biofilter with the diameter and effective length of 0.115 m and 0.8 m, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations